ACTIVITIES OF RAIDING GROUPS OF THE UIA IN THE TERRITORY OF THE KAMIANETS-PODILSKYI REGION IN 1943–1944 - KOMARNITSKY, Oleksandr (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article is devoted to the study of raids by Ukrainian insurgent army (UIA) divisions on the territory of Kamianets-Podilskyi region in 1943–1944 and is part of the vector of research on large-scale raids on the territory of Soviet Ukraine with the aim of expanding the network of UIA-East groups and raising an anti-Bolshevik uprising. Considering the fact that in historiography it was known about the existence of derivative groups, only after accessing the archives and digitizing the array of documents and materials, it became possible to outline their scale, which reached as far as the town of Dzhankoy in the south and the Don River in the east. Moreover, the theme of the national liberation movement was constantly discredited by racist propaganda and their agents inside Ukraine. The Russian-Ukrainian war and the victories of the Ukrainians in this war logically strengthen society's demand for research into the problems of the liberation movement. It is natural that recently the number of qualitative studies on the subject has increased significantly, one of the reasons is the significant source base and the number of scientific centres. Worthy of attention are the materials of the Organization of Ukrainian nationalists (OUN) archive, the edition of the Chronicle of the UIA, the works of V. Horbatyuk, N. Myzak, P. Mirchuk, I. Patrilyak, V. Serhiychuk, L. Shankovsky and many other authors. Such developments of historiography, multiplied by the source material, make it possible to highlight the scale of the raids of the UIA departments, to analyse their purpose, organizational features, and the results of their conduct. The reasons for the raids lie in the OUN's concept of restoring Ukraine's independence in its ethnic borders and their approbation after the act of restoring Ukraine's independence on June 30, 1941, and the first migration groups to the east. Such activities were eliminated by the repressive bodies of the Soviet Union with the movement of the front to the west, therefore, after the creation of the UIA, the leadership of the OUN repeated this attempt. Kamianets-Podilskyi region was located immediately near the epicenter of OUN activity in Halychyna and Volyn, through which two major routes passed. The tasks of the derivative groups were reconnaissance, establishment of communication channels, underground apartments, recruitment of new recruits into the ranks of the UIA, development of the youth movement, and educational activities among both the youth and the adult population. It should be noted that from the very beginning of the raids from 1943 to April 1944, the UIA units successfully fought not only against the Nazi occupation forces, but also against the Soviet occupation forces. By the decision of R. Shukhevich, in 1944, the Podilsk Regional District was created as part of the Ternopil, Chortkiv, and Kamianets-Podilsky Districts.